Approach-Related Complications of Anterior Lumbar Interbody Fusion: Results of a Combined Spine and Vascular Surgical Team. (March 2016) - Mobbs, Ralph J.; Phan, Kevin; Daly, Daniel; Rao, Prashanth J.; Lennox, Andrew
Study Design: Retrospective analysis of prospectively collected cohort data. Objective: Anterior lumbar interbody fusion (ALIF) is a commonly performed procedure for the treatment of degenerative diseases of the lumbar spine. Detailed and comprehensive descriptions of intra- and postoperative complications of ALIF are surprisingly limited in the literature. In this report, we describe our experience with a team model for ALIF and report all complications occurring in our patient series. Methods: Patients were prospectively enrolled between January 2009 and January 2013 by a combined spine surgeon and vascular surgeon team. All patients underwent an open ALIF using an anterior approach to the lumbosacral spine. Results: From the 227 ALIF cases, mean operative blood loss was 103 mL, ranging from 30 to 900 mL. Mean operative time was 78 minutes. The average length of stay was 5.2 days. Intraoperative vascular injury requiring primary repair with suturing occurred in 15 patients (6.6%). There were 2 cases of postoperative retroperitoneal hematoma. Three patients (1.3%) had incisional hernia requiring revision surgery; 7 (3.1%) patients had prolonged ileus (>7 days) managed conservatively. Four patients described retrograde ejaculation. Sympathetic dysfunction occurred in 15 (6.6%) patients. There were 5 (2.2%) cases of superficial wound infection treated with oral antibiotics, with no deep wound infections requiring reoperation or intravenous therapy. There were no mortalities in this series. Conclusions: ALIF is a safe procedure when performed by a combined vascular surgeon and spine surgeon team with acceptably low complication rates. Our series confirms that the team approach results in short operative times and length of stay, with rapid control of intraoperative vessel injury and low overall blood loss.